Digital Photography - Buckingham, Alan (London Dorling Kindersley, 2005)
Introduction to digital photography, with tips and techniques for taking photographs, and manipulating images on the computer. Suggested level: intermediate, secondary.
Include Index and Glossary
Keywords: Photography--Digital techniques